Probability and statistics for finance - Rachev, S. T. [ (Svetlozar Todorov)] (The Frank J. Fabozzi series, 2010)
"A comprehensive look at how probability and statistics is applied to the investment process Finance has become increasingly more quantitative, drawing on techniques in probability and statistics that many finance practitioners have not had exposure to before. In order to keep up, you need a firm understanding of this discipline. Probability and Statistics for Finance addresses this issue by showing you how to apply quantitative methods to portfolios, and in all matter of your practices, in a clear, concise manner. Informative and accessible, this guide starts off with the basics and builds to an intermediate level of mastery. Outlines an array of topics in probability and statistics and how to apply them in the world of finance. Includes detailed discussions of descriptive statistics, basic probability theory, inductive statistics, and multivariate analysis. Offers real-world illustrations of the issues addressed throughout the text. The authors cover a wide range of topics in this book, which can be used by all finance professionals as well as students aspiring to enter the field of finance"-- Provided by publisher